Morphological Changes in Oral Organs and Tissues in Women after Menopause and their Analysis - Islamova Nilufar Bustanovna; Abdulaxatov Abdugaffor Abdusattor ugli (Scientific Trends, 2024)
During menopause, irreversible changes in the hormonal function of the ovaries occur, the concentration of estrogens decreases. It is during this period that a progressive increase in various diseases is noted [8]. The study of the dental status in menopausal women has proven the existence of a relationship between a decrease in estrogen concentration and a sharp increase in dental diseases [4]. Because the oral mucosa and salivary glands contain estrogen receptors, changes in hormonal levels can be seen directly in the mouth. Leimola-Virtanen et al confirmed the presence of estrogen mRNA and immunoreactive protein in the oral mucosa and salivary glands, which also confirms its biological role [11]. Thus, the climacteric period is characterized by a disorder of metabolism and function in the tissues of the oral cavity [6]. As a result, tooth loss, periodontal disease, increased bone resorption of the alveolar processes are observed.
Keywords: Menopause, generalized periodontitis, postmenopausal period, diseases of the oral mucosa.